CONDOLENCE MECHANISMS OF DRUGS USED IN THE DISEASE OF HEART FAILURE (Academia Science Repository, 2023)
Dear reader, in this article we want to provide information about the drugs used in heart failure, one of the important diseases that are now common . Heart failure — sometimes known as congestive heart failure — occurs when the heart muscle doesn't pump blood as well as it should. When this happens, blood often backs up and fluid can build up in the lungs, causing shortness of breath.Certain heart conditions, such as narrowed arteries in the heart (coronary artery disease) or high blood pressure, gradually leave the heart too weak or stiff to fill and pump blood properly.Proper treatment can improve the signs and symptoms of heart failure and may help some people live longer. Lifestyle changes — such as losing weight, exercising, reducing salt (sodium) in your diet and managing stress — can improve your quality of life. However, heart failure can be life-threatening. People with heart failure may have severe symptoms, and some may need a heart transplant or a ventricular assist device (VAD).One way to prevent heart failure is to prevent and control conditions that can cause it, such as coronary artery disease, high blood pressure, diabetes and obesity.